How to give and receive critism - Mc Callum, Brian; Kienzle, Andy; Communication Briefings; RAC Productions (Alexandria, VA : Communication Briefings, 1997)
This video showed the right way to give and receive critism to help everyone in your organization succeed
Content provided by Morey Stettner author of'The art of winning conversation'
Executive producer, Brian Mc Callum ; script writer, Andy Kienzle
Keywords: Critism, Personal; Helping behavior; Success